2023
DOI: 10.1017/jns.2023.8
|View full text |Cite
|
Sign up to set email alerts
|

Association between a priori and a posteriori dietary patterns and the risk of type 2 diabetes: a representative cohort study in Taiwan

Abstract: The present study aimed to investigate the relationship between dietary patterns and the risk of type 2 diabetes mellitus (T2DM) among Taiwanese individuals. Data were collected using a nationwide cohort study (2001–15) from the Triple-High Database. Dietary intake was assessed using the twenty-group food frequency questionnaire and used to calculate alternate Mediterranean diet (aMED) and Dietary Approaches to Stop Hypertension (DASH) scores. Principal component analysis (PCA) and partial least-squares (PLS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Consistently, a previous meta-analysis of 10 prospective cohort studies including 404,528 participants, revealed that high adherence to "healthy" dietary patterns signi cantly decreased the risk of type 2 DM(RR:0.86; 95%CI:0.82-0.90) (40). However, in contrast to our ndings, found no signi cant association between adherence to the DASH diet and DM (35)(36). Although evidence associating DASH diet to DM remains inconsistent, some possible mechanisms have been reported to explain the observed negative association.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Consistently, a previous meta-analysis of 10 prospective cohort studies including 404,528 participants, revealed that high adherence to "healthy" dietary patterns signi cantly decreased the risk of type 2 DM(RR:0.86; 95%CI:0.82-0.90) (40). However, in contrast to our ndings, found no signi cant association between adherence to the DASH diet and DM (35)(36). Although evidence associating DASH diet to DM remains inconsistent, some possible mechanisms have been reported to explain the observed negative association.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, the remaining thirty-seven full-text articles were examined for eligibility, and 22 were excluded for the following reasons: 5 did not evaluated DM risk; 1 lacked su cient data and the corresponding author of this study could not be contacted; 16 did not mention DASH diet score. Finally, fteen studies(13 cohort and 2 case-control studies) with 557,475 participants and 57,064 cases of DM were included for this systematic review and meta-analysis(6-8, [19][20][21][22][23][24][25][26][34][35][36][37]. Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations